Executive Control in Depressive Rumination: Backward Inhibition and Non-inhibitory Switching Performance in a Modified Mixed Antisaccade Task - Lo, Barbara C. Y.; Liu, Jeffrey C. C. (Frontiers in Psychology, 2017)
Background and Objectives: The present study examines backward inhibition and non-inhibitory switching performance among depressed and healthy participants in a modified mixed antisaccade task. Specifically, sad and neutral faces were incorporated in the design to examine executive control difficulties associated with brooding trait. Methods: Thirty-nine participants took part in the study, including 19 depressed patients and 20 healthy control subjects. Participants completed a diagnostic interview and self-report questionnaires, including the Beck Depression Inventory and Ruminative Response Scale-Brooding Subscale. They were then instructed to complete prosaccade and antisaccade trials in the pure and mixed blocks whereby eye gazes were tracked to assess inhibition and switching efficiency. Results: For the switching effects, a significant group x brooding x task type interaction was found as hypothesized when multilevel modeling analysis was employed. Switching deficits associated with brooding was found to be greatest when sad faces were presented to depressed group. No significant results in backward inhibition or error rates were observed. Conclusions: The patterns observed suggest that as opposed to backward inhibition, set shifting difficulty associated with brooding trait may be modulated by negative mood and cognition. In future research, emotional faces other than sad faces may be used to further explore if the observations could be generalized to other affective conditions.